In-situ Tem observation of Pd Catalyzed Graphene growth by current-induced annealing - Mohamad Saufi bin Rosmi, Siti Munirah Binti Sidik (Tanjung Malim, 2024)
In-situ Tem observation of Pd Catalyzed Graphene growth by current-induced annealing by Mohamad Saufi bin Rosmi, Siti Munirah Binti Sidik